(untitled) - Myers, Anne (Pacific Grove, CA, 1996)
Designed with the beginning researcher in mind, this book leads students through the entire research process from generating testable hypotheses to writing the research report. The major sections of the book parallel the major sections of the research report (introduction, method, results, and discussion), allowing students to see the relationship between designing and conducting an experiment, analyzing and interpreting the research findings, and reporting those findings.
Keywords: Psychology, Experimental,Tâm lý học, thí nghiệm